Practice of Local Wisdom among the Muslim’s Indigenous Community of Mah Meri in Tanjung Sepat, Banting, Selangor (Melayu: Jurnal Antarabangsa Dunia Melayu, 2025)
Local wisdom refers to a set of cutoms or norms within a community that are passed down through generations. The term custom encompasses various aspects of community life involving normative beliefs and behaviours inherited from their ancestors. In general, the implementation of customs is still significant among the Orang Asli community. This is due to the animist culture and beliefs that still surround the Orang Asli community. However, when the community transitioned from animistic beliefs to embracing Islam, a shift in belief systems occured, which impacted the practice of the original customs of the Mah Meri Orang Asli. Therefore, this paper identifies the customs that are still practised, analyses the factors leading to the abandonment of certain customs and explains the adaptation local wisdom within Islamic teachings among the Mah Meri Muslim Orang Asli community in Tanjung Sepat, Banting, Selangor as the basis of the debate. The methodology used is qualitative in the form of ethnography. Interviews and follow-up observations methods were also used to achieve the objectives of this study. The results of the study show that certain customary practices are still carried out as cultural norms, but are not related to ancestral beliefs. Most abandoned practices are due to differering religious concepts, while some have been adapted to fit the religious teachings. This study is expected to be the basis for more in-depth studies in the future.Full text: PDF